Throughput and product quality control for a grinding mill circuit using non-linear MPC. (June 2016) - le Roux, J.D.; Olivier, L.E.; Naidoo, M.A.; Padhi, R.; Craig, I.K.
Abstract : Highlights: Proposal of a nonlinear model-based control architecture for a grinding mill circuit. Use nonlinear MPC for the overall grinding circuit and dynamic inversion control for the fast sump dynamics. Achievement of independent control of throughput and product quality. Full-state feedback not assumed. Observers make use of real-time continuous measurements commonly available on industrial plants. Abstract: A non-linear model-based control architecture for a single-stage grinding mill circuit closed with a hydrocyclone is proposed. The control architecture aims to achieve independent control of circuit throughput and product quality, and consists of a non-linear model predictive controller for grinding mill circuit control, and a dynamic inversion controller to control the fast sump dynamics. A particle filter is used to estimate the mill states, and an algebraic routine is used to estimate the sump states. The observers make use of real-time continuous measurements commonly available on industrial plants. Simulation results show that control objectives can be achieved by the controller despite the presence of measurement noise and disturbances.